THE CORRELATION OF MATERNAL AGE AND GESTATIONAL AGE WITH ANEMIA IN PREGNANT WOMEN AT PUSKESMAS MERAURAK, TUBAN, EAST JAVA, INDONESIA - Erna Eka Wijayanti Wijayanti; Umu Qonitun Qonitun (International Journal of Midwifery Research, 2021)
Anemia is an indicator of poor nutrition and poor health. Anemia in pregnant women is strongly associated with maternal and infant mortality and morbidity, including the risk of miscarriage, stillbirth, prematurity, and low birth weight. This researsh was to analyze The Correlation Of Maternal Age And Gestational Age With Anemia In Pregnant Women At Puskesmas Meraurak, Tuban, East Java, Indonesia. The research was an observational analytic with a cross-sectional approach. This research data collection tool is secondary data by looking at medical records. The time this research began in May - July 2021 at the Meraurak Health Center, Tuban. The population in this study were all pregnant women, whether anemic or not, who visited the Merakurak Tuban Health Center in 2021. The sampling technique used in this study was total sampling. The sample in this study was 30 respondents.. Data analysis in this study used Contingency Coefficient with the help of SPSS. Significant limitation if p-value < 0.05. There is a correlation between maternal age and the incidence of anemia in pregnant women and there is no correlation between gestational age and the incidence of anemia in pregnant women. Pregnant women are advised to consume at least 90 iron tablets during pregnancy.